Hydrocarbons conversion to syngas in inert porous media combustion - Toledo Torres, Mario; Gracia, Francisco; Caro, Sebastián; Gómez, Jaime; Jovicic, Vojislav (International Journal of Hydrogen Energy, 2016)
Experimental combustion in inert porous media of Liquefied Petroleum Gas (LPG), Butane, Propane, Diesel Fuel and Heavy Fuel Oil (HFO) is presented to assess the syngas production within different stages of refinement of fuels, considering light gases up to a residual oil. The porous media is composed by a fixed bed of alumina spheres and temperatures and gas composition were acquired while stable combustion waves under rich fuel conditions were produced. The results of this study showed that it is possible to partially oxidize HFO producing up to a 10% of H2 and CO in the products for the equivalence ratio of f ¼ 1.3, with a superior performance than any other fuel tested in this work. The behavior of the recorded temperature results showed good agreement with the available literature. Upstream regimes of propagation of the combustion wave are observed for the experiments with liquid fuels, while gaseous fuels presented downstream regimes for f > 2 up to f ¼ 4. Results suggest that in order to efficiently transform the fuels into syngas, it is convenient to operate the reactor under an upstream regime considering the chemical energy at inlet and outlet. Furthermore, liquid fuels, regardless of its refining level, have the potential to produce syngas in inert porous media in promising volumes.<br
UnivIS-Import:2017-07-10:Pub.2016.tech.ITC.stmmec.hydroc
Keywords: Hydrogen; Syngas; Diesel; LPG; Heavy fuel oil; Inert porous media combustion